Partially Covered Self-Expandable Metal Stents versus Polyethylene Stents for Malignant Biliary Obstruction: A Cost-Effectiveness Analysis. Issue 7 (2015) - Barkun, Alan N; Adam, Viviane; Martel, Myriam; AlNaamani, Khalid; Moses, Peter L
Abstract : BACKGROUND/OBJECTIVE: Partially covered self-expandable metal stents (SEMS) and polyethylene stents (PES) are both commonly used in the palliation of malignant biliary obstruction. Although SEMS are significantly more expensive, they are more efficacious than PES. Accordingly, a cost-effectiveness analysis was performed. METHODS: A cost-effectiveness analysis compared the approach of initial placement of PES versus SEMS for the study population. Patients with malignant biliary obstruction underwent an endoscopic retrograde cholangiopancreatography to insert the initial stent. If the insertion failed, a percutaneous transhepatic cholangiogram was performed. If stent occlusion occurred, a PES was inserted at repeat endoscopic retrograde cholangiopancreatography, either in an outpatient setting or after admission to hospital if cholangitis was present. A third-party payer perspective was adopted. Effectiveness was expressed as the likelihood of no occlusion over the one-year adopted time horizon. Probabilities were based on a contemporary randomized clinical trial, and costs were issued from national references. Deterministic and probabilistic sensitivity analyses were performed. RESULTS: A PES-first strategy was both more expensive and less efficacious than an SEMS-first approach. The mean per-patient costs were US6, 701 for initial SEMS and US20, 671 for initial PES, which were associated with effectiveness probabilities of 65.6% and 13.9%, respectively. Sensitivity analyses confirmed the robustness of these results. CONCLUSION: At the time of initial endoscopic drainage for patients with malignant biliary obstruction undergoing palliative stenting, an initial SEMS insertion approach was both more effective and less costly than a PES-first strategy.